P.1.19 Increased benefit generosity and the impact on workers' compensation claiming behaviour: an interrupted time series study in victoria, australia. (April 2019) - Lane, Tyler; Gray, Shannon; Sheehan, Luke; Collie, Alex
Abstract : Objective: To measure the effect of legislated increases to workers' compensation benefits on claiming behaviour. Methods: Interrupted time series of workers' compensation claims in Victoria, Australia (2008–2012), assessing 1) the overall effect of the legislation and 2) raising the wage replacement cap on higher earners, by condition type, in reference to a comparator of other Australian workers' compensation jurisdictions. Results: Overall claiming increased 11.7%, driven largely by musculoskeletal condition claims. There was no detectable effect on disability duration overall, though back/neck conditions were up 26.9%. Among higher earners, there was mixed evidence of an increase in claiming, though disability durations were up 32.9%, which was also driven by back/neck conditions. There was mixed evidence of an effect on mental health claims, suggesting either no response or a negative response to benefit generosity. Conclusions: Findings mainly align with existing evidence: more generous benefits increase claiming and disability durations, primarily driven by back/neck musculoskeletal conditions. However, some mixed findings by injury group and among higher earners raise questions about confounders such as co-occurring events.